Prevalence of Underweight, Overweight, and Obesity in Adults in Bhaktapur, Nepal in 2015–2017 - Schwinger, Catherine; Chandyo, Ram K.; Ulak, Manjeswori; Hysing, Mari; Shrestha, Merina; Ranjitkar, Suman; Strand, Tor A. (Frontiers in Nutrition, 2020)
Introduction There is an increase in the double burden of malnutrition globally, with a particular rise in Asia. In Nepal, undernutrition has been prevalent for decades. Today, however, the incidence of overweight and obesity (OWOB) in the country has increased substantially. There is a need to conduct local studies reporting on the concurrent burden of both underweight and OWOB across adult populations. This study addresses this need by describing the distribution of body mass index (BMI) in a defined population of adults living in the peri-urban community of Bhaktapur, Nepal. Material and methods For this cross-sectional analysis, we used data that were available from 600 women and 445 men whose children were enrolled in an individually randomized, double-blind, placebo-controlled trial assessing the effect of daily vitamin B12 supplementation. Upon enrolment of their 6–11-month-old children, mothers and fathers were interviewed about their socio-demographic details. In addition, their weight and height were measured by trained field workers. Each parent’s BMI was calculated as the ratio of body weight (in kg) and height squared (in m), expressed as kg/m2, and categorized according to the WHO recommendation. We used linear and multinomial regression models to assess associations between the BMI of the mothers and fathers, and their baseline characteristics. Results The mean BMI was 23.7 kg/m2 for both the mothers and fathers with a standard deviation (SD) of 3.6 and 3.7, respectively. The proportion categorized as underweight, overweight and obese was also similar in the two groups with around 5% being underweight, 30% being overweight and 5% being obese. Age was positively associated with BMI in both groups. Those categorized as daily wage earner had a lower mean BMI than those in other occupational groups. Conclusion Our results contribute to documenting the burden of both under- and overnutrition in a selected group of young adults living in a peri-urban community in Nepal. As Nepal is undergoing an improvement in its economic situation, as well as a nutrition transition, it is important to provide sufficient information to enable timely action, and evidence-based decision-making to prevent a further increase in Nepal’s growing double burden of malnutrition.